Neonatal and Fetal Outcomes of Pregnant Mothers with Hypertensive Disorder of Pregnancy at Hospitals in Wolaita Zone, Southern Ethiopia - Mohammed Obsa; Eskinder Wolka Woticha; Bedilu Girma Weji; Blen Kassahun Dessu; Getahun Dendir Wolde; Bereket Gebremskel Girmay; Eyasu Tamru Bakru; Lemi Belay; Mohammed Hussein Gediye; Negeso Gobena Kute; Misrak W/yohannes Menchamo (Mashhad University of Medical Sciences, 2019)
Background & aim: Hypertensive disorders of pregnancy are among the severe medical disorders peculiar to pregnancy. It is one of the risk factors during pregnancy either for the mother or fetus or both. Therefore, this study aimed to assess fetal and neonatal outcomes of mothers with hypertensive disorders of Pregnancy. Methods: This hospital-based cross-sectional study was conducted on neonates born from June 20 to November 20, 2014 at hospitals in Wolaita zone, Southern Ethiopia. The check lists of the study conducted on Prevalence of Hypertension and Complications of Hypertensive Disorders in Pregnancy in patients visiting in the Delivery Ward of Valiasr Hospital were used as base and then modified before being used in our study. Data were analysed using Epi Info (version 7) and SPSS (version 20). Bivariate and multivariate analyses were used to identify factors associated with perinatal outcomes. Analysis were used to identify factors associated with perinatal outcome. Results: Preeclampsia and eclampsia can adversely affect the wellbeing of the fetuses and neonates. Nulliparous women were about five times more likely to develop unfavorable outcome in comparison with multiparous women (AOR 4.85; 95% CI: 0.064-12.442). Conclusion: Hypertensive disorder of pregnancy is associated with the increased risk of adverse fetal and neonatal outcome. Therefore, it is of utmost importance to have timely diagnosis and appropriate care.